Correlation of histomorphological pattern of cardiac amyloid deposition with amyloid type: a histological and proteomic analysis of 108 cases. Issue 5 (28th September 2015) - Larsen, Brandon T; Mereuta, Oana M; Dasari, Surendra; Fayyaz, Ahmed U; Theis, Jason D; Vrana, Julie A; Grogan, Martha; Dogan, Ahmet; Dispenzieri, Angela; Edwards, William D; Kurtin, Paul J; Maleszewski, Joseph J
Abstract : Aims: Prognostication and treatment selection for cardiac amyloidosis requires accurate amyloid typing. The aim of this study was to investigate the utility of histomorphology for predicting type. Methods and results: Autopsy cases with cardiac amyloidosis (1998–2010) were typed by the use of mass spectrometry‐based proteomics. Deposition patterns were correlated with amyloid type. Among 108 decedents (mean age 75 years; 69% men), 107 had a single type, including transthyretin (ATTR) (60 cases), amyloid light chain (AL) (32 λ; 12 κ), amyloid A (AA) (two), and apolipoprotein AIV (AApoAIV) (one). Interstitial deposition was more extensive in AL amyloidosis cases than in ATTR cases [odds ratio (OR) 6.8, P = 0.0004]. Histomorphological patterns of interstitial deposition were mixed in 61% of AL amyloidosis cases and in 61% of ATTR cases, but diffuse pericellular deposits favoured AL amyloidosis (OR 10.7, P = 0.0001), nodular deposits favoured ATTR (OR 3.1, P = 0.0229), and discrete pericellular deposits tended to partially favour ATTR (OR 1.7, P = 0.1970). Arterial and venous deposits each favoured AL amyloidosis (OR ranging from 9.3 to 192.0, P‐value ranging from 0.0022 to <0.0001), and were severe in AL amyloidosis. Endocardial deposits favoured AL amyloidosis (OR 46.3, P < 0.0001) and were also more severe in AL amyloidosis. Conclusions: The extent and distribution of cardiac amyloidosis strongly correlate with amyloid type, suggesting fundamental differences in the pathobiology of deposition. The tendency for mixed patterns to occur limits the practicality and accuracy of using histopathology for amyloid typing.